Comparative evaluation of otolith and fin ray as tools for assessing population differentiation in Atlantic sturgeon (Acipenser oxyrinchus) - Simon Bernatchez; Louis Landry-Massicotte; Yves Paradis; Olivier Morissette; Anne-Lise Fortin; Sabrina Villeneuve; Léon L’Italien; Pascal Sirois (PLoS ONE, 2026)
Atlantic sturgeon ( Acipenser oxyrinchus Mitchill, 1815) is a long-lived, anadromous species known for its extensive migrations between freshwater and marine habitats throughout its life. Despite increased conservation efforts, there is only limited information on the early life stages and habitat use of the St. Lawrence River (SLR) and Saint John River (SJR) populations in Eastern Canada. This study explores the use of otolith and fin ray microchemistry to distinguish Atlantic sturgeon populations and investigate habitat use throughout their lives. The otoliths and fin rays of fish caught in both the SLR and SJR regions were analyzed using LA-ICP-MS procedures to determine their elemental signatures throughout their lifespan (coretoedge). Using a machine learning classification approach, both otolith and fin ray revealed strong potentials for differentiating individuals from the SLR and SJR populations. Fin ray microchemistry showed a higher reclassification success and produced more contrasted elemental signatures compared to otolith microchemistry. Our results also showed that the integration of elements is dependent on the structure (i.e., fin ray or otolith). A significant correlation between element concentrations at the core of fin rays and otoliths was observed for only three elements (Sr, Mn, and Li). This phenomenon should be further investigated and considered in future applications because it could lead to reclassification errors. These findings suggest that fin ray microchemistry is a powerful approach that can be used to discriminate population origin and infer life history patterns of Atlantic sturgeon. These results are especially relevant since we propose a cost-effective method to monitor population structure and habitat use without lethal sampling. This is an essential step toward careful management of this species in Eastern Canada.